The population history of the Philippines a genetic overview - Delfin, Frederick C. (Philippine Studies: Historical and Ethnographic Viewpoints, 2015)
This professorial address synthesizes the findings of several studies on the genetics of Philippine population groups and presents them in a manner accessible to nonspecialists. These studies examined different types of DNA (Y-chromosome, mitochondrial, and autosomal) samples contributed by participants in twelve regional centers and nineteen ethnolinguistic groups. The data reveal (a) genetic affinities with different groups in the Asia-Pacific region, (b) genetic signals of ancient demographic events, (c) an ancient genetic history of about 5,000?50,000 years ago, and (d) a complex population genetic structure. This genetic overview has implications for the study of human history, forensics, and medicine.